Abundance and habitat suitability of Siamese crocodiles (Crocodylus siamensis, Schneider 1801) in Phetchaburi River, Kaeng Krachan National Park, Thailand - KASIDIS CHANPRADUB; ANAK PATTANAWIBOOL; APINYA SAISAMORN; NARIS BHUMPAKPHAN; SOMJATE CHANTHANA; CHARONG THONGSONG; YAN OUANSING; WARONG SUKSAWATE; RONGLARP SUKMASUANG (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Chanpradub K, Pattanawibool A, Saisamorn A, Bhumpakphan N, Chanthana S, Thongsong C, Ouansing Y, Suksawate W, Sukmasuang R. 2023. Abundance and habitat suitability of Siamese crocodiles (Crocodylus siamensis, Schneider 1801) in Phetchaburi River, Kaeng Krachan National Park, Thailand. Biodiversitas 24: 4755-4765. The Siamese crocodile (Crocodylus siamensis, Schneider 1801) is one of the critically endangered species with a remnant population reported in Kaeng Krachan National Park. This study aimed to investigate Siamese crocodiles' abundance and habitats along the Phetchaburi River. Thirteen rafting trips from December 2021 to July 2023 were conducted at a total distance of 315 kilometers, recording 68 encounters with an encounter rate of 0.22 per kilometer. It was estimated that the population size of Siamese crocodiles was four individuals. Environmental factors that influenced crocodile distribution, with slope, elevation, forest types, cumulative flow rates upstream, and land use patterns, were identified. These findings underscore the significance of the Phetchaburi River area for freshwater crocodile conservation, as indicated by a highly reliable model with a reliable score of 0.99±0.02. Important recommendations include habitat protection, development of a crocodile threat surveillance system, ongoing population studies, and community involvement, which are essential for sustainable conservation practices, public awareness campaigns, captive breeding and reintroduction programs, and population restoration efforts. This research provides valuable insights into the habitats and environmental factors impacting Siamese crocodiles, highlighting the critical role of preserving Kaeng Krachan National Park as an important habitat for this species.